Flavonolignans from silymarin modulate antibiotic resistance and virulence in Staphylococcus aureus - Holasová, Kateřina; Křížkovská, Bára; Hoang, Lan; Dobiasová, Simona; Lipov, Jan; Macek, Tomáš; Křen, Vladimír; Valentová, Kateřina; Ruml, Tomáš; Viktorová, Jitka (Biomedicine & pharmacotherapy, 2022)
Antibiotic resistance is currently a serious health problem. Since the discovery of new antibiotics no longer seems to be a sufficient tool in the fight against multidrug-resistant infections, adjuvant (combination) therapy is gaining in importance as well as reducing bacterial virulence. Silymarin is a complex of flavonoids and flavonolignans known for its broad spectrum of biological activities, including its ability to modulate drug resistance in cancer. This work aimed to test eleven, optically pure silymarin flavonolignans for their ability to reverse the multidrug resistance phenotype of Staphylococcus aureus and reduce its virulence. Silybin A, 2,3-dehydrosilybin B, and 2,3-dehydrosilybin AB completely reversed antibiotic resistance at concentrations of 20 µM or less. Both 2,3-dehydrosilybin B and AB decreased the antibiotic-induced gene expression of representative efflux pumps belonging to the major facilitator (MFS), multidrug and toxic compound extrusion (MATE), and ATP-binding cassette (ABC) families. 2,3-Dehydrosilybin B also inhibited ethidium bromide accumulation and efflux in a clinical isolate whose NorA and MdeA overproduction was induced by antibiotics. Most of the tested flavonolignans reduced cell-to-cell communication on a tetrahydrofuran-borate (autoinducer-2) basis, with isosilychristin leading the way followed by 2,3-dehydrosilybin A and AB, which halved communication at 10 µM. Anhydrosilychristin was the only compound that reduced communication based on acyl-homoserine lactone (autoinducer 1), with an IC50 of 4.8 µM. Except for isosilychristin and anhydrosilychristin, all of the flavonolignans inhibited S. aureus surface colonization, with 2,3-dehydrosilybin A being the most active (IC50 10.6 µM). In conclusion, the selected flavonolignans, particularly derivatives of 2,3-dehydrosilybin B, 2,3-dehydrosilybin AB, and silybin A are non-toxic modulators of S. aureus multidrug resistance and can decrease the virulence of the bacterium, which deserves further detailed research.
Keywords: Silychristin; Anti-Bacterial Agents; virulence; antibiotická rezistence; Silybin; Staphylococcal Infections; Flavonolignans; silymarin; stafylokokové infekce; Staphylococcus aureus; Silymarin; silibinin; Virulence; Humans; antibakteriální látky; Efflux pump; Drug Resistance, Microbial; Multidrug resistance; lidé